A theoretical model of the mechanism of entrepreneurial leadership attributes and leadership behaviours on nursing team creativity in a new hospital: a grounded theory study - Jing Gong; Lorna Kwai Ping Suen; Binxu Yang; Yifei Yang; Xintong Deng; Jing Zhou (BMC Nursing)
Abstract Background A new hospital is a recently established healthcare organization, recognized by Chinese law, that can provide medical services to meet the health needs of the population and has been in operation for no more than 42 months. However, new hospitals face several challenges, including low market acceptance, healthcare quality and safety issues, a shortage of healthcare personnel, and the time required to build patient trust. As a result, they experience greater uncertainty compared to established hospitals. Nurses play a vital role as health promoters in new hospitals. Nursing team creativity refers to the ability of team members to use creative thinking and methods to solve problems in the nursing service process. This ability helps medical institutions adapt to the changing healthcare environment and deliver better, more efficient, and sustainable health services. Entrepreneurial leadership is a style of leadership that inspires and guides employees to explore strategic values and seek opportunities. Research has shown that entrepreneurial leadership is crucial in fostering creativity among nurses. It encourages nurses to explore and utilize entrepreneurial opportunities, positively impacting their organizations’ development. While many studies have used quantitative data to examine how entrepreneurial leadership influences team creativity through mediating variables, few have focused on the interactive qualities and intrinsic motivations between entrepreneurial leadership and team creativity. Grounded Theory is a qualitative research method that emphasizes a dynamic, step-by-step process of collecting and analyzing real-world data to generate theories. Therefore, this study uses Grounded Theory to explore the interactive qualities and leadership behaviors that promote nursing team creativity within the Chinese cultural context. Methods Data were collected from a new hospital in Guizhou, China, using purposive and theoretical sampling techniques. Participants included 15 nursing managers and 14 nursing team members. Semi-structured interviews were conducted from April 2023 to July 2023. The data were analyzed using NVivo software, and the reporting follows the Consolidated Criteria for Reporting Qualitative Research guidelines. Results The study identified five core attributes of entrepreneurial leadership and two types of leadership behaviors. These explain the interactive process nursing managers use to stimulate creativity in their teams within new hospitals. The leadership attributes include achievement orientation, flexibility and patience, concerns and questions, communication and sharing and execution and support. The entrepreneurial leadership behaviors were categorized into positive and negative behaviors Conclusion Nursing managers in new hospitals can enhance their teams’ creativity and health-promoting capabilities by applying the five entrepreneurial leadership attributes and actively practicing the positive leadership behaviors identified in this study. Avoiding negative leadership behaviors may also help stimulate creativity and guide nurses in implementing their ideas in clinical practice.